PENGARUH FINANCING TO DEPOSIT RATIO (FDR), BIAYA OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL (BOPO), DAN RETURN ON ASSET (ROA) TERHADAP FINANCIAL DISTRESS PADA BANK UMUM SYARIAH DI INDONESIA TAHUN 2020-2024 - Fika Aryani; Ahmad Winanto (Jurnal Akuntansi dan Pajak, 2027)
This study aims to analyze the effect of Financing to Deposit Ratio (FDR), Operating Expenses to Operating Income (BOPO), and Return on Assets (ROA) on Financial Distress in Islamic Commercial Banks in Indonesia during the period 2020–2024. This research employs a quantitative approach using secondary data obtained from the annual financial reports of Islamic Commercial Banks published by the Financial Services Authority (OJK) and the official websites of each bank. The population of this study consists of all Islamic Commercial Banks registered with the Financial Services Authority (OJK) during the 2020–2024 period. The sampling technique used is purposive sampling. Data analysis is conducted using panel data regression analysis with the assistance of statistical software. The results of this study are expected to provide an overview of the influence of liquidity, operational efficiency, and profitability ratios on financial distress conditions in Islamic Commercial Banks in Indonesia. Furthermore, this study is expected to serve as an early warning system for bank management in detecting potential financial distress at an early stage.